2019
DOI: 10.1097/pra.0000000000000359
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Reviews on the Safety of Electroconvulsive Therapy Administered During Pregnancy

Abstract: Objective: To inform obstetricians and psychiatrists about the safety of electroconvulsive therapy (ECT) administration during pregnancy and to reconcile conflicting recommendations concerning this treatment. Methods: A systematically conducted overview was undertaken on the safety of ECT during pregnancy. The Cochrane Library, MEDLINE/ PubMed, PsycINFO, and Ovid were independently searched by 2 of the authors from January 2015 to March 2017 using the following search terms: electroconvulsive therapy, ECT, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…There have been five systematic reviews of the safety of ECT in pregnancy since 2015 (Calaway et al, 2016; Coshal et al, 2019; Leiknes et al, 2015; Sinha et al, 2017; Spodniakova et al, 2015), with Calaway et al, focusing on the safety of ECT in the first trimester. These overlapping reviews examined several hundred case reports and concluded that ECT in pregnancy was relatively safe.…”
Section: Treatmentsmentioning
confidence: 99%
“…There have been five systematic reviews of the safety of ECT in pregnancy since 2015 (Calaway et al, 2016; Coshal et al, 2019; Leiknes et al, 2015; Sinha et al, 2017; Spodniakova et al, 2015), with Calaway et al, focusing on the safety of ECT in the first trimester. These overlapping reviews examined several hundred case reports and concluded that ECT in pregnancy was relatively safe.…”
Section: Treatmentsmentioning
confidence: 99%
“…Other clinical indications for ECT as a first-line treatment for an episode of MDD include treatment resistance or repeated medication intolerance in a prior episode, a prior favorable response to ECT, and patient preference (58). (54,55,58,(61)(62)(63). In stark contrast with these guidelines, the National Institute for Health and Care Excellence (NICE) states that ECT should only be used 'to achieve rapid and short-term improvement of severe symptoms after an adequate trial of other treatment options has proven ineffective and/or when the condition is considered to be potentially life-threatening, in individuals with severe depressive illness, catatonia, or a prolonged or severe manic episode' (56).…”
Section: Pregnancy and Postpartummentioning
confidence: 99%
“…Guidelines around this have been published. 131,134 ECT has been shown to be relatively safe in pregnancy, [135][136][137] in the elderly, 138 and in children and adolescents, 92,139 though some have challenged that safety data on ECT in children with autism were not systematically collected. 116 It has been demonstrated definitively that ECT does not cause structural brain damage, 140 even in patients who have received hundreds of lifetime treatments.…”
Section: Dovepressmentioning
confidence: 99%